Powder and method for producing the same, and method for producing a resin composition
Patent Information
- Application Number
- JP2025060152
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0007】 本発明者らは、高密度粒子を低密度粒子に結合させて複合粒子を形成することにより、上記課題を解決できることを見いだした。すなわち、本発明による粉体は、中空粒子を含む粉体であって、粉体の平均粒子密度が0.7~1.5g/cm3であり、粉体の粒度分布を測定したとき、粒子径D90の1/5以下の粒子径を持つ粒子が全体の10%体積以下であり、面積円形度0.8未満の粒子が全体の10体積%以上含まれている。複合粒子は分散媒中で懸濁する粒子となりやすいため、分散性が高い分散液となる。
Smart Images

Figure 2026166910000001
Abstract
Description
Technical Field
[0001] The present invention relates to a powder suitable as a filler for semiconductor insulating materials. In particular, the present invention relates to a powder containing hollow particles having various densities.
Background Art
[0002] In recent years, high speed and large capacity have been advanced in information and communications. For this reason, materials used for communication devices are required to have a low dielectric constant (low Dk) and a low dielectric loss tangent (low Df). For example, insulating materials having a low dielectric constant and a low dielectric loss tangent are required for printed wiring boards on which semiconductor elements are mounted.
[0003] A filler is blended into the insulating material from the viewpoints of durability (rigidity), heat resistance and the like. In order to realize a low dielectric constant and a low dielectric loss tangent, silica hollow particles are widely used as fillers. In addition, the filler is also required not to impair the filterability and injectability of the insulating material-forming liquid in the manufacturing process of the insulating material. It is also known to use hollow particles having a particle size distribution with at least two or more peaks as a filler for coating films (see, for example, Patent Document 1). It is also known to obtain a filler from a dispersion liquid containing hollow particles having various porosities in order to realize a low dielectric constant and a low dielectric loss tangent (see, for example, Patent Document 2).
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Patent Document 2
Summary of the Invention
Problems to be Solved by the Invention
[0005] As described in Patent Document 1, in dispersions containing hollow particles of various particle sizes, hollow particles with varying porosity exist. As a result, particles with high and low particle densities are mixed together. Particles with high particle density settle in the dispersion, while particles with low particle density float. In recent years, in order to achieve weight reduction, low dielectric constant, and low dielectric loss tangent, there has been a demand for a large amount of particles with high porosity, i.e., low-density particles. This inevitably leads to a large number of particles floating in the dispersion medium, resulting in the problem that particles cannot be uniformly dispersed in the dispersion.
[0006] In this document, particles dispersed in the dispersion medium are referred to as suspended particles, lighter particles floating in the upper layer (near the liquid surface) are referred to as suspended particles, and particles that remain settled in the lower layer (near the bottom) are referred to as settled particles. [Means for solving the problem]
[0007] The inventors have found that the above problem can be solved by bonding high-density particles to low-density particles to form composite particles. That is, the powder according to the present invention is a powder containing hollow particles, and the average particle density of the powder is 0.7 to 1.5 g / cm³. 3 When the particle size distribution of the powder is measured, particles with a particle size of 1 / 5 or less of the particle diameter D90 account for less than 10% of the total volume, and particles with an area circularity of less than 0.8 account for more than 10% of the total volume. Since composite particles tend to become suspended particles in the dispersion medium, they result in a highly dispersible dispersion.
[0008] Furthermore, the powder manufacturing method according to the present invention comprises: a first step of preparing a particle group containing high-density particles and low-density particles by spray-drying an aqueous alkali silicate solution in a hot air stream; a second step of removing alkali contained in the particle group; a third step of heating the slurry obtained in the second step while applying shear force until the water content is 10% by mass or less, thereby bonding the high-density particles around the low-density particles and forming composite particles; and a fourth step of calcining the composite particles. [Modes for carrying out the invention]
[0009] The powder according to the present invention is a powder containing hollow particles of various particle densities, wherein the average particle density of the powder is 0.7 to 1.5 g / cm³. 3 When the particle size distribution of the powder is measured, particles with a particle size of 1 / 5 or less of the particle diameter D90 account for 10% or less of the total volume, and particles with an area circularity of less than 0.8 account for 10% or more of the total volume. Such powders contain composite particles in which multiple high-density particles are bonded around low-density particles. Typically, high-density particles have a smaller diameter than low-density particles. The aforementioned composite particle structure is achieved because it is more stable for smaller particles to adhere around larger particles. To attach high-density particles to low-density particles, moisture on the particle surface can be utilized. If there is about 1-10% moisture on the particle surface, high-density particles are more likely to adhere to low-density particles. Porous particles can easily hold moisture in this range. Furthermore, it is preferable for the particles to contain a large amount of silica. When moisture is removed from the attachment area, the SiOH groups of both particles undergo dehydration condensation and bond. Low-density particles and high-density particles may also be bonded using another component such as a silane coupling material. Composite particles in which high-density particles are bonded to low-density particles do not separate even when filled into resin and exhibit high dispersibility.
[0010] Furthermore, when attaching high-density particles to low-density particles, it is preferable to vibrate the powder dispersion or otherwise fluidize the particles so that they come into contact with each other. As the dispersion concentrates when heated in this fluidized state, small particles (high-density particles) are coated onto the surface of large particles (low-density particles). As the moisture content between particles decreases, bonds are formed between the particles.
[0011] The following describes the properties of powders containing composite particles. a) Surface state of the particles The surface condition of the particles affects the bonding between low-density and high-density particles. In the process of forming composite particles, a porous particle surface is preferable. Porous particles can contain about 1 to 10% by mass of moisture, making them easier to adhere uniformly. With less than 1% by mass of moisture, it is difficult to obtain a state where low-density and high-density particles adhere together. Furthermore, if the moisture content in the composite process is less than 10% by mass, it is possible to prevent adhesion between high-density particles and the adhesion of high-density particles in two layers to low-density particles. For the final powder, a non-porous particle surface is preferable due to its effect on dielectric properties.
[0012] b) Angle of repose The angle of repose of a powder refers to the angle of the conical slope that naturally forms when the powder is piled on a flat surface, and it indicates the powder's fluidity. A smaller angle of repose indicates higher powder fluidity. An angle of repose of 40 degrees or less is preferable.
[0013] [Method for producing powder] The present invention provides a method for producing powder, comprising: a first step of preparing a particle group containing high-density and low-density particles by spray-drying an aqueous alkali silicate solution in a hot air stream; a second step of removing alkali contained in the particle group; a third step of heating the slurry obtained in the second step while applying shear force until the moisture content is 10% by mass or less, thereby bonding the high-density particles around the low-density particles and forming composite particles; and a fourth step of calcining the composite particles. Furthermore, it is preferable to include a classification step to remove fine particles and coarse particles after at least one of the third and fourth steps. Other steps, such as a drying step, may be included between each step.
[0014] The following describes each step in detail. (First step) In this process, silica-based particles are granulated by spray-drying an alkaline silicate aqueous solution in a hot air stream. While this process is performed to obtain hollow particles, it is difficult to produce only hollow particles, and the granulated hollow particles may consequently contain solid particles. In this case, the solid particles fall into the category of high-density particles.
[0015] The molar ratio of SiO2 to M2O (where M is an alkali metal) in alkali silicate (SiO2 / M2O) is preferably 1 to 5, and more preferably 2 to 4. If this molar ratio is less than 1, the amount of alkali is too high, making it difficult to remove it sufficiently even with acid washing in the alkali removal process. Furthermore, the deliquescent properties of the spray-dried product increase, making it difficult to obtain the desired hollow particles. If this molar ratio exceeds 5, the solubility of the alkali silicate decreases, making it difficult to prepare an aqueous solution. Even if an aqueous solution can be prepared, it may not be possible to form hollow particles by spray drying.
[0016] The concentration of SiO2 in the alkali silicate aqueous solution is preferably 1 to 30% by mass, and more preferably 5 to 28% by mass. Although production is possible at concentrations below 1% by mass, productivity is significantly reduced. If the concentration exceeds 30% by mass, the stability of the alkali silicate aqueous solution decreases significantly, resulting in high viscosity, and spray drying may not be possible. Even if spray drying is possible, the particle size distribution, outer shell thickness, etc., become extremely non-uniform, which may limit the applications of the resulting particles. As the alkali silicate, water-soluble sodium silicate and potassium silicate can be used. Sodium silicate is preferred.
[0017] Conventional known methods such as the rotating disk method, the pressurized nozzle method, and the two-fluid nozzle method can be used as spray drying methods. In this case, the two-fluid nozzle method is preferred.
[0018] In spray drying, the inlet temperature of the spray dryer is preferably 300 to 600°C, and more preferably 350 to 550°C. The outlet temperature is preferably 120 to 300°C, and more preferably 130 to 250°C. With these temperature settings, hollow particles can be obtained stably.
[0019] (Second process) Next, the alkali contained in the particles granulated in the first step is removed. A method of removing the alkali by adding an acid for neutralization is suitable. A treatment of immersing the particles in an acid solution is preferred. At this time, the molar ratio (Ma / Msp) between the number of moles of M₂O (Msp) in the particles and the number of moles of the acid (Ma) is preferably 0.6 to 4.7, more preferably 1 to 4.5. When this molar ratio is less than 0.6, the amount of the acid relative to M₂O is too small. Therefore, the silica skeleton formation of silicic acid, which is considered to occur concurrently with the removal of the alkali, does not proceed, and the particles may partially dissolve, or the dissolved alkali silicate may gel. Even if the molar ratio exceeds 4.7, the silica skeleton formation does not proceed further, and the acid is excessive, which is not economical.
[0020] Further, it is preferable to immerse the particles in the aqueous acid solution such that the concentration of the particles is 1 to 30 mass% in terms of SiO₂. When the concentration is less than 1 mass%, there is no problem in alkali removal or detergency, but the production efficiency decreases. When the concentration exceeds 30 mass%, the concentration is too high, which may reduce the alkali removal and washing efficiency. 5 to 25 mass% is more preferable.
[0021] The conditions for immersion in the aqueous acid solution are not particularly limited as long as the alkali can be removed to a desired amount, and usually, the treatment temperature is 5 to 100°C, and the treatment time is 0.5 to 24 hours. After the immersion treatment, washing by a conventionally known method is preferred, for example, filtration and washing with pure water. If necessary, the above acid treatment and washing may be repeated.
[0022] As the acid used in this step, mineral acids (hydrochloric acid, nitric acid, sulfuric acid, etc.) and organic acids (acetic acid, tartaric acid, malic acid, etc.) can be used. Mineral acids are preferably used, and in particular, sulfuric acid with a high valence is preferred.
[0023] (Third Step) The washed slurry obtained in the second step was heated while applying a shear force until the water content became 10 mass% or less. Thereby, particles in a composite state (composite particles) were obtained (compositing step).
[0024] (Fourth Step) Next, the particles after the compounding process are fired. The firing temperature is preferably 600 to 1200°C, and more preferably 900 to 1100°C. If the firing temperature is below 600°C, a large amount of SiOH groups remain, and the dielectric loss tangent of the particles becomes high. Therefore, even when compounded into the resin, it is difficult to obtain a dielectric loss tangent reduction effect. If the firing temperature exceeds 1200°C, the particles sinter easily, so irregularly shaped particles and coarse particles are likely to be generated. This causes a decrease in the filterability and injectability of the resin composition.
[0025] (Classification process) By performing a classification process between the first and fourth steps, fine and coarse particles are removed. If the classification process is performed before alkali removal, it is necessary to perform the classification process immediately after granulation to prevent hollow particles from absorbing moisture (deliquescent) and agglomerating or adhering together. Alternatively, if the classification process is performed before calcination, it may be performed immediately after the alkali removal process.
[0026] The classification process can reduce the amount of individual low-density and high-density particles.
[0027] Classifiers used in dry classification can be broadly classified into gravity classifiers, inertial classifiers, and centrifugal classifiers. More precise classification is possible by using inertial or centrifugal classifiers. Examples of classifiers that can precisely classify even light particles that are not easily subjected to centrifugal force include the Elbow Jet manufactured by Nippon Steel Mining Co., Ltd., the SG Separator manufactured by 3M Japan, the AeroFine Classifier manufactured by Nisshin Engineering Co., Ltd., and the MicroSpin manufactured by Nippon Pneumatic Mfg. Co., Ltd. Among these, the Elbow Jet and AeroFine Classifier are preferred.
[0028] Classifiers used in wet classification can be broadly classified into gravity classifiers and centrifugal classifiers in principle. Using a centrifugal classifier allows for more precise classification. Examples of classifiers that can precisely classify even light particles that are difficult to apply centrifugal force to include the Hydrocyclone manufactured by Nippon Chemical Machinery Industry Co., Ltd., the Superclon manufactured by Murata Industries, Ltd., and the iClassifier manufactured by Satake Chemical Machinery Industry Co., Ltd. Among these, the iClassifier is preferred. With wet classification, when removing fine particles, coarse particles with a low specific gravity can also be removed, thereby increasing the classification efficiency.
[0029] The removal of fine and coarse particles may be performed simultaneously or separately. When performed separately, the order of removal may be either fine or coarse particles. Furthermore, each process of removing fine and coarse particles may be performed in multiple stages.
[0030] Furthermore, a drying process may be included as appropriate during the manufacturing process. The drying process can be included between the compounding process and the classification process, between the classification process and firing, both, or between the compounding process and firing. It may be included multiple times as needed. Alternatively, the drying process may be performed before firing, and the classification process may be performed between the drying process and firing. To better enjoy the effects of the present invention, it is preferable to perform the classification process after the drying process and then firing. Heat drying is suitable as the drying process. The drying temperature is preferably 50 to 400°C, and more preferably 50 to 200°C. Specifically, examples include drying at a low temperature of about 50 to 200°C over a long period of time, drying by gradually increasing the temperature, and drying by changing the temperature in several stages.
[0031] Furthermore, it is preferable to perform a sieving process to remove particle clumps at least one of the following stages: after drying and after firing. Note that particle clumps refer to, for example, particles with a diameter exceeding 50 μm, and a sieve with an appropriate mesh size (number of meshes) that can remove such particle clumps should be used.
[0032] [Resin composition] A resin composition is prepared by blending a powder containing composite particles with a resin material. Such a resin composition can be used as an insulating material for electronic materials such as semiconductors, specifically for copper-clad laminates, prepregs, and build-up films used to form printed circuit boards (including rigid and flexible substrates). It can also be used for semiconductor packaging-related materials such as mold resins, mold underfills, and underfills, as well as adhesives for flexible substrates.
[0033] As the resin, curable resins commonly used in electronic materials such as semiconductors can be used. Photocurable resins are also acceptable, but thermosetting resins are preferred. Examples of curable resins include epoxy resins, polyphenylene ether resins, fluorine resins, polyimide resins, bismaleimide resins, acrylic resins, methacrylic resins, silicone resins, BT resins, cyanate resins, and the like. Furthermore, examples of epoxy resins include bisphenol-type epoxy resins, novolac-type epoxy resins, triphenolalkane-type epoxy resins, epoxy resins having a biphenyl skeleton, epoxy resins having a naphthalene skeleton, dicyclopentadienephenol novolac resins, phenol aralkyl-type epoxy resins, glycidyl ester-type epoxy resins, alicyclic epoxy resins, heterocyclic epoxy resins, halogenated epoxy resins, and the like. These resins may be used individually or in mixtures of two or more types.
[0034] The resin composition preferably contains powder A and curable resin B in a mass ratio (A / B) of 10 / 100 to 95 / 100. This allows the resin composition to fully exhibit its function as a filler while maintaining its properties such as fluidity. A mass ratio (A / B) of 30 / 100 to 80 / 100 is more preferable.
[0035] Furthermore, the resin composition preferably contains curing agents such as phenol compounds, amine compounds, and acid anhydrides. When epoxy resin is used as the curable resin, examples of curing agents include resins having two or more phenolic hydroxyl groups in one molecule (phenol resins such as bisphenol-type resins, novolac resins, triphenolalkane-type resins, resol-type phenol resins, phenol aralkyl resins, biphenyl-type phenol resins, naphthalene-type phenol resins, and cyclopentadiene-type phenol resins), and acid anhydrides such as methylhexahydrophthalic acid, methyltetrahydrophthalic acid, and methylnadic anhydride. Various additives (colorants, stress relaxants, defoamers, leveling agents, coupling agents, flame retardants, curing accelerators, etc.) may be added to the resin composition as needed.
[0036] Conventional methods can be used to produce the resin composition. For example, a curable resin, powder, curing agent, additives, etc., can be mixed and kneaded in a roll mill or the like. The resulting resin composition can be applied to a substrate and cured by heat, ultraviolet light, etc.
[0037] The powder can be mixed directly with the resin, or a dispersion of the powder in an organic solvent can be prepared first, and then this dispersion can be mixed with the resin material.
[0038] The following describes specific embodiments of the present invention. [Example 1] 30,000 g of an aqueous water glass solution (SiO2 / Na2O molar ratio 3.2, SiO2 concentration 24% by mass) was used. Hollow particles were obtained by spraying hot air at an inlet temperature of 400°C into one of two fluid nozzles at a flow rate of 0.62 kg / hr and into the other nozzle at a flow rate of 31,800 L / hr (air / liquid volume ratio 63,600). At this time, the outlet temperature was 150°C (hollow particle preparation process).
[0039] Next, 5000g of hollow particles were immersed in 32000g of a 10% by mass sulfuric acid aqueous solution and stirred for 15 hours. At this time, the solid content (SiO2) concentration was 10.2% by mass, the temperature of the dispersion was 35°C, and the pH was 3.0. The molar ratio (Ma) / (Msp) of the number of moles of acid (Ma) was 1.2. After the immersion treatment, the sulfuric acid was removed by solid-liquid separation, and the alkali was removed by washing with pure water. This yielded a slurry with 50% by mass of hollow particles dispersed in water (alkali removal step). The slurry was heated while applying shear force until the water content was 10% by mass or less, to obtain composite particles (composite particles) (composite formation step).
[0040] Next, the material was dried in a dryer at 120°C for 24 hours (drying process). After drying, it was crushed and sieved through a 75 μm mesh sieve to remove coarse particles. Next, using a proprietary cyclone, a dry centrifugal classification process was performed with a flow rate of 5 m / s in the powder transport line (classification process). Particles that passed through without being captured by the cyclone were recovered using a bag filter. Furthermore, the classified particles were heat-treated at 1000°C for 10 hours to reduce the moisture content to less than 1% (calcination process). This yielded a powder containing composite particles. After calcination, particle clumps (foreign matter) were removed using a sieve with a mesh size of 150 μm.
[0041] The physical properties of the powder containing the composite particles obtained as described above were measured and evaluated as follows. The results are shown in Table 1.
[0042] (1) Average particle density The average density of particles contained in the powder was determined using a gas pycnometer method with nitrogen gas, employing a Quantachrome Instruments Ultrapyc5000.
[0043] (2) Area circularity The sample was added to pure water with a dispersant to create a dispersion with a particle concentration of 0.05% by weight, and then irradiated with ultrasound. Using this dispersion, measurements were performed on approximately 50,000 particles using a Malvern Panalytic Morphologi 4. The distribution of equivalent circle diameter was defined as the particle size distribution. Area circularity was defined by squaring the circumference of a circle with the same area as the projected object divided by the perimeter of the object (circularity). The ratio of the volume of particles with an area circularity of less than 0.8 was calculated.
[0044] (3) Particle size distribution The sample was added to pure water with a dispersant to create a dispersion with a particle concentration of 0.05% by mass, and then irradiated with ultrasound. Using this dispersion, measurements were performed on approximately 50,000 particles using a Malvern Panalytic Morphologi 4. From the distribution of equivalent circle diameters, the volume ratio of D90 and particles with a volume less than 1 / 5 of D90 was determined.
[0045] (4) Layer distribution of powder The sample (powder) was suspended in NMP (N-methyl-2-pyrrolidone) at a 40% volume concentration, and the solution was allowed to stand for 24 hours. The upper layer (suspended particles), dispersed layer (suspended particles), and lower layer (settled particles) were then separated and dried at 100°C for 2 hours. The percentage of mass of each layer was then calculated.
[0046] (5)Angle of repose The angle of repose was measured using a powder tester (manufactured by Hosokawa Micron Corporation). The angle of repose of a powder refers to the angle of the conical slope that is naturally formed when the powder is piled on a flat surface, and it indicates the fluidity of the powder. A smaller angle of repose indicates higher powder fluidity.
[0047] [Example 2] Except for using 30,000 g of an aqueous water glass solution (SiO2 / Na2O molar ratio 3.3, SiO2 concentration 24% by mass), the procedure was the same as in Example 1 to obtain a powder containing composite particles.
[0048] [Comparative Example 1] The compounding process was not performed. Otherwise, the powder was obtained by processing in the same manner as in Example 1.
[0049] Table 1
Claims
1. A powder containing hollow particles, The average particle density of the aforementioned powder is 0.7 to 1.5 g / cm³. 3 When the particle size distribution of the aforementioned powder was measured, particles with a particle size of 1 / 5 or less of the particle size D90 accounted for 10% or less of the total volume. A powder characterized by containing 10% or more by volume of hollow particles with an area circularity of less than 0.
8.
2. The powder according to claim 1, wherein the angle of repose is 40 degrees or less.
3. The powder according to claim 1, wherein when the powder is suspended in NMP (N-methyl-2-pyrrolidone) at a volume of 40%, and the solution is allowed to stand for 24 hours, the amount of suspended particles is 10% by mass or less, the amount of suspended particles is 80% by mass or more, and the amount of settled particles is 10% by mass or less.
4. A method for producing a resin composition, characterized by incorporating the powder described in claim 1 into a resin material.
5. The first step involves preparing a particle group containing high-density and low-density particles by spray-drying an alkaline silicate aqueous solution in a hot air stream, A second step involves removing alkali contained in the aforementioned group of particles, A third step involves heating the slurry obtained in the second step while applying shear force until the water content is 10% by mass or less, thereby bonding the high-density particles around the low-density particles and forming composite particles. A method for producing powder, characterized by comprising a fourth step of calcining the composite particles.
Citation Information
Patent Citations
Hollow particle and filler material for heat insulation coating
JP2017031235A
Powder, production method therefor, and resin composition production method
WO2022210919A1